PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA DAN KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS X SMA N 2 TONDANO - Selty Anastasia Tindige; Jeane Cornelda Rende; Alfrits Komansilan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This study aims to: 1) To find out how to improve physics learning outcomes of Class X students at SMA Negeri 2 Tondano, use a project-based learning model on effort and energy. 2) Determination of the improvement in the abilities of class X students in physics processes at the SMA Negeri 2 Tondano using a project-based learning model, on the subject of effort and energy. This type of research is a research using the Classroom Action Research Method (PTK) done in 2 cycles in 4 stages, namely: planning phase, action, observation and reflection. The results of the study were 1) The application of the PjBL learning model on the subject of effort and energy can improve the learning outcomes of the physical and scientific process skills of the class X SMA N 2 Tondano. 2) Cycle I The gain test value was 0.43 in the medium category, Cycle II the gain test value was 0.51 in the moderate category. 3) In the first cycle the average value of the scientific process skills was 84.7 with a good category and cycle II the average value of the scientific process skills was 89.9 with a very good category.